Spatial pattern of the environmental exposure to tin in the vicinity of an alloy industry in Volta Redonda, Rio de Janeiro State, Brazil - Sayonara Vieira de Azevedo; Andrea Sobral; Maria de Fátima Ramos Moreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: Despite being widely used in industry, the literature on tin and its effects in humans is scarce, especially regarding reference values in biological indicators such as blood and urine. Similarly, environmental limits are also rare. This study sought to assess the spatial distribution of hotspots in the environmental exposure to tin in the vicinity of an alloy industry in the south region of the state of Rio de Janeiro, Brazil. The study population consisted of 74 adults. Graphite furnace atomic absorption spectrometry determined tin in all samples. Households and points around the industry were georeferenced with the use of GPS to identify the most intense tin sites. Results of the first and second campaigns ranged from 0.022 to 0.153 and 0.003 to 0.445µg m-3 for the atmospheric air, whereas such ranges were 0.64 to 1.61 and 1.97 to 8.54µg m-2 for household dust, respectively. The mean tin concentration found in the blood of the population was 3.85 ± 1.57µg L-1. In urine the value was 3.56 ± 1.88µg L-1. The kernel map showed the highest spatial concentrations of tin in household dust in the eastern region of the industry. In the first sampling, atmospheric air samples presented the most elevated concentrations in the southwest and southeast. Although the direction of the wind was northwest, potentially high risks were concentrated in the central area in the second collection. The largest hotspots were in the north, south and southeast regions; however, urine samples showed medium to high levels in the west and east regions. Regarding blood samples, the greatest difference was the absence of hotspot areas in the west. Environmental monitoring becomes necessary to better assess the exposure to tin.